73 Effect of subacute ruminal acidosis (SARA) and Saccharomyces cerevisiae fermentation products on gastrointestinal microbiome of dairy cows. (7th December 2018) - Guo, J; Zhang, Z; Derakhshani, H; Yoon, I; Plaizier, J; Khafipour, E
Abstract: Subacute ruminal acidosis caused by high-grain feeding can cause dysbiosis of the rumen microbiome, which is associated with the pathogenesis of the rumen disorders. Saccharomyces cerevisiae fermentation products (SCFP) have been widely used as rumen fermentation modifiers to stabilize the rumen conditions. The objective of this study was to investigate if SCFP can attenuate the impact of SARA on microbial communities in the rumen. Thirty two Holstein lactating dairy cows were assigned into four treatment groups (n=8/trt) that received a base TMR (34.9 DM NDF, 18.6 % DM starch) supplemented daily with 1) 140 g of ground corn (Control), 2) 14 g Diamond V Original XPC TM mixed in 126 g of ground corn (XPC), 3) 19 g Diamond V NutriTek® mixed in 121 g of ground corn (NTL), and 4) 38 g Diamond V NutriTek® mixed in 102 g of ground corn (NTH) in a randomized complete block design. The experiment lasted from 4 weeks before until 12 weeks after calving. The SARA challenges were conducted on week 5 (SARA1) and 8 (SARA2) after calving by replacing 20% of the base TMR with pellets containing 50% barley and 50% wheat. Rumen liquid and solid samples were collected weekly. DNA was extracted from each sample and subjected to Illumina sequencing of V1–V2 regions of 16S rRNA gene and analyzed by QIIME2. Differential abundance analysis with gneiss was used to analyze the microbial composition. Alpha- and beta-diversities were analyzed using MIXED procedure of SAS and PERMANOVA, respectively. Both SARA challenges decreased ( P < 0.05) richness and evenness of rumen liquid and solid microbial communities in the control, XPC and NTL groups. NTH treatment however prevented these reductions in the rumen liquid microbiota during SARA challenges. Supplementation with NTH was able to prevent rumen microbiota from losing their diversity during the SARA challenges.